An in vitro model of drug-resistant seizures for selecting clinically effective antiseizure medications in Febrile Infection-Related Epilepsy Syndrome - Cerovic, Milica; Di Nunzio, Martina; Craparotta, Ilaria; Vezzani, Annamaria (Frontiers in Neurology, 2023)
Introduction FIRES is a rare epileptic encephalopathy induced by acute unremitting seizures that occur suddenly in healthy children or young adults after a febrile illness in the preceding 2 weeks. This condition results in high mortality, neurological disability, and drug-resistant epilepsy. The development of new therapeutics is hampered by the lack of validated experimental models. Our goal was to address this unmet need by providing a simple tool for rapid throughput screening of new therapies that target pathological inflammatory mechanisms in FIRES. The model was not intended to mimic the etiopathogenesis of FIRES which is still unknown, but to reproduce salient features of its clinical presentation such as the age, the cytokine storm and the refractoriness of epileptic activity to antiseizure medications (ASMs). Methods We refined an in vitro model of mouse hippocampal/temporal cortex acute slices where drug-resistant epileptic activity is induced by zero Mg2+/100 μM 4-aminopirydine. Clinical evidence suggests that acute unremitting seizures in FIRES are promoted by neuroinflammation triggered in the brain by the preceding infection. We mimicked this inflammatory component by exposing slices for 30 min to 10 μg/ml lipopolysaccharide (LPS). Results LPS induced a sustained neuroinflammatory response, as shown by increased mRNA levels of IL-1β, CXCL1 (IL-8), TNF, and increased IL-1β/IL-1Ra ratio. Epileptiform activity was exacerbated by neuroinflammation, also displaying increased resistance to maximal therapeutic concentrations of midazolam (100 μM), phenytoin (50 μM), sodium valproate (800 μM), and phenobarbital (100 μM). Treatment of LPS-exposed slices with two immunomodulatory drugs, a mouse anti-IL-6 receptor antibody (100 μM) corresponding to tocilizumab in humans, or anakinra (1.3 μM) which blocks the IL-1 receptor type 1, delayed the onset of epileptiform events and strongly reduced the ASM-resistant epileptiform activity evoked by neuroinflammation. These drugs were shown to reduce ASM-refractory seizures in FIRES patients. Discussion The neuroinflammatory component and the pharmacological responsiveness of epileptiform events provide a proof-of-concept validation of this in vitro model for the rapid selection of new treatments for acute ASM-refractory seizures in FIRES.